(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
We conducted a systematic examination of water quality, specifically faecal contamination of drinking water, in the Warwade Dam water in our current study. Our goal was to measure physical characteristics (temperature, pH, conductivity, and total dissolved solids) as well as the presence of faecal coliforms (E. coli and total coliforms) in Warwade Dam water, which is used as a source of drinking water for people who live near the dam. This data collection will be used as a baseline for future monitoring and access to drinkable water. The sample locations were chosen based on their principal use as a source of drinking water for the Warwade population. In general, physical parameters have little correlation, but there are weak relationships between total coliform data and increasing temperature and pH. During the dry season, our research clearly shows the existence of bacterial faecal contamination indicators. More E. coli and coliform germs were found in samples from more densely inhabited locations